Strategies of Achieving Work-Life Balance Among Married Female Journalists of Taraba State Broadcasting Service (TSBS) Jalingo - Garison, Anthony; Tsokwa, Solomon Blessing; Mahmud, Umar Al-amin (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
In order to reconcile their demanding professional and family commitments, married female journalists frequently confront particular difficulties. The strategies married female journalists use to strike a work-life balance, the effects of such strategies on the mechanisms to aid them overcome the challenges are examined in this study. This research uses in-depth interview, to examine the coping strategies, networks of support, and self-care routines these women employ to manage the demands of their careers and personal lives. The results show that they synergize with their colleagues to meet up, they also have to work ahead of time. It was also revealed that excessive demands and responsibilities lead to conflict leading to increased stress and anxiety due to conflicting demands and responsibilities. The study used Role Conflict Theory which proposes that individuals experience conflict when trying to fulfill multiple roles (e.g., work, family, personal), leading to stress, anxiety, and decreased performance. The theory holds that, excessive demands and responsibilities lead to conflict and that incompatible demands and expectations from different roles also lead to conflict. The study recommends that media stations should recognize and reward hardworking married female Journalists, implement gender sensitive policies like parental leave, childcare. Married Female Journalists should employ maids to relief them of domestic duties; and stations should provide creches for married Female Journalists to take care of their babies. The study contributes to our understanding of the complex interplay between work and family life among married female journalists, providing insights for promoting their well-being and career sustainability.